Optical imaging and spectroscopy - Brady, David J. (David Jones), 1961- (Wiley, 2008)
Optical Imaging and Spectroscopy establishes the analytical framework of the emerging discipline of computational imaging. The text explains how to construct system models for diverse optical designs and how to use these system models to quantify performance metrics. Such models are essential to the analysis and design of digital imaging and spectroscopy systems. The text includes: Direct and simple exposition of the interface between continuous fields and discrete representations, including wavelet analysis, discretization on focal planes, multiplex measurement and compressive sampling.